A COMPARATIVE STUDY ON THE IMPACT OF SOCIAL SUPPORT AND ACADEMIC SELF-EFFICACY ON UNDERGRADUATE PSYCHOLOGY STUDENTS’ STRESS LEVEL AND COPING MECHANISMS - Akeredolu, Adekunle Yemi; Adebayo, Sulaiman Olanrewaju; Adekola, Busayo Mary; Dada, Olugbenga David; Oluwajuyitan, Femi Raphael (African Journal of Social and Behavioural Sciences, 2025)
Psychology students increasingly report high stress levels and difficulties adopting effective coping strategies, raising concerns about factors that either buffer or intensify this stress. This necessitated examining the relationships among social support, academic self-efficacy, stress levels, and coping mechanisms among undergraduate psychology students at Ekiti State University (EKSU) and Federal University Oye-Ekiti (FUOYE). A total of 190 students (81 males, 109 females) participated, with 104 from EKSU and 86 from FUOYE. Correlation analysis indicated that students with higher academic self-efficacy experience lower stress levels (r =- 0.21, p < .01), avoidant coping strategies showed a positive correlation with stress levels (r = 0.22, p < 01), and emotion-focused coping was positively associated with stress (r = 0.16, p < 05). Social support from family, friends, and significant others was positively correlated with both emotion-focused and problem-focused coping mechanisms. Regression analyses revealed that social support significantly predicted emotion-focused (β = 0.22, p < .01) and problem-focused (β = 0.28, p < .01) coping strategies. Conversely, academic self- efficacy negatively predicted avoidant coping (β =- 0. 31, p <. .01). Stress levels also significantly predicted both avoidant (β = 0. 16, p <. .05) and emotion- focused coping (β = 0. 16, p <. .05). Mediation analysis revealed that academic self-efficacy and stress partially mediated the relationship between social support and coping mechanisms by reducing the direct effect of social support after being severally introduced to the model as mediators. A Multivariate Analysis of Variance (MANOVA) showed that neither academic level (F(1, 186) = 0.02, p > .05) nor institution (F(1, 186) = 265, p > .05) produced a significant main effect on these variables. Findings suggest that interventions that enhance academic self-efficacy and social support networks could effectively help students manage stress and adopt more adaptive coping mechanisms.